Pengaruh Sertifikasi Halal Dan Kesadaran Halal Terhadap Keputusan Pembelian Produk Kosmetik Wardah Di Desa Bangun Rejo Tanjung Morawa - Dwi Putri Pratiwi; Adrial Falahi (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2023)
This study aims to analyze and examine the Effect of Halal Certification and Halal Awareness on the PurchaseDecision of Wardah Cosmetics Products in Bangun Rejo Village, Tanjung Morawa. This research uses quantitative research. The population in this study was the community in Bangun Rejo Village, Tanjung Morawa who used wardah products, female and Muslim aged 17-50 years with a total of 400, with sampling using the slovin formula as many as 80 respondents. The sampling method used in this study is Simple Random Sampling. The results of this study were collected through a questionnaire which was analyzed using multiple linear regression. The test results show that the variables of halal certification and halal awareness partially have a positive and significant effect on purchasing decisions, and the results of the F test prove that the variables of halal certification and halal awareness simultaneously have a positive and significant effect on purchasing decisions. Furthermore, Adjusted R Square is 0.671, which means that the relationship variable between halal certification and halal awareness on purchasing decisions is 67.1%, while the remaining 32.9% can be explained by other variables not examined in this study. The R Square value is 0.679 and the standard error of the estimate is 1.377, which means the smaller the standard deviation, the better the model. Keywords : Halal Certification, Halal Awareness, Purchase Decision